Exploring the Potential of Differentiated Instruction for Improving Literacy-Technology Integration in the Coffee Value Chain - Maspul, Kurniawan Arif (Novatio : Journal of Management Technology and Innovation, 2024)
The study looks into how individualized education might increase literacy-technology integration in the Saudi coffee value chain. The project intends to provide insights and recommendations for coffee educators, policymakers, and industry stakeholders by investigating the significance of literacy, differentiated education, technology integration, and relevant theories. The study investigates literacy-technology integration experiences, difficulties, and opportunities using qualitative methodologies such as observations and talks with industry experts. The findings emphasize the value of collaborative alliances, focused professional development, digital learning tools, research, and assessment mechanisms in increasing literacy-technology integration in the Saudi coffee sector. These initiatives have the potential to promote knowledge enhancement, innovation, and long-term growth in the sector.